Corrosive poisonings in adults - Andon Chibishev; Zanina Pereska; Vesna Chibisheva; Natasha Simonovska (ScopeMed Publishing, 2012)
Ingestion of corrosive substances may cause severe to serious injuries of the upper gastrointestinal tract and the poisoning can even result in death. Acute corrosive intoxications pose a major problem in clinical toxicology since the most commonly affected population are the young with psychic disorders, suicidal intent and alcohol addiction. The golden standard for determination of the grade and extent of the lesion is esophagogastroduodenoscopy performed in the first 12-24 hours following corrosive ingestion. The most common late complications are esophageal stenosis, gastric stenosis of the antrum and pyloris, and rarely carcinoma of the upper gastrointestinal tract. Treatment of the acute corrosive intoxications include: neutralization of corrosive agents, antibiotics, anti-secretory therapy, nutritional support, collagen synthesis inhibitors, esophageal dilation and stent placement, and surgery.
Keywords: corrosive substances; esophageal injuries; esophagogastroduodenoscopy; postcorrosive stenosis; sodium hydroxid